The expression of hate speech against Afro-descendant, Roma, and LGBTQ+ communities in YouTube comments - Carvalho, P.; Caled, D.; Silva, C.; Batista, F.; Ribeiro, R. (Journal of Language Aggression and Conflict, 2024)
This paper addresses the specificities of online hate speech against the Afro-descendant, Roma, and LGBTQ+ communities in Portugal. The research is based on the analysis of CO-HATE, a corpus composed of 20,590 YouTube comments, which were manually annotated following detailed guidelines created for that purpose. We applied methods from corpus linguistics to assess the prevalence of overt and covert hate speech, counter-speech, and offensive speech, considering different grounds of discrimination, and to investigate the main linguistic and rhetorical strategies underlying hatred messages. The research results highlight the importance of tackling covert hate speech, a recurring phenomenon often anchored in irony and fallacious argumentation, including the emotional appeal to fear and the implicit call to action. We believe this study will aid in advancing the analysis of online hate speech, while promoting the development of efficient automated detection models, specifically regarding the Portuguese language.